American sniper : the autobiography of the most lethal sniper in U.S. military history /: the autobiography of the most lethal sniper in U.S. military history. (2013) - Kyle, Chris, 1974-2013; DeFelice, Jim, 1956-; McEwen, Scott
No abstract available